1995
DOI: 10.1104/pp.109.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Urease Is Not Essential for Ureide Degradation in Soybean

Abstract: The hypothesis that soybean (Clycine max 1. [Merrill]) catabolizes ureides to urea to a physiologically significant extent was tested and rejected. Urease-negative (eu3-el/eu3-el) plants were supported by fixed N, or by 2 mM NH,NO,, so that xylem-borne nitrogen contained predominantly ureides (allantoin and allantoic acid) or amide amino acids, respectively. Seed nitrogen yield was equal on either nitrogen regime, although 35-d-old fixing plants accumulated about 6 times more leaf urea. In callus, lack of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 34 publications
6
32
0
1
Order By: Relevance
“…Arg degradation by arginase during germination is consistent with the sharp increase in urea in urease-deficient mutant seedlings (Fig. 6;Stebbins and Polacco, 1995). Urease has been proposed to function coordinately with arginase in the utilization of seed protein reserves during germination (Thompson, 1980).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Arg degradation by arginase during germination is consistent with the sharp increase in urea in urease-deficient mutant seedlings (Fig. 6;Stebbins and Polacco, 1995). Urease has been proposed to function coordinately with arginase in the utilization of seed protein reserves during germination (Thompson, 1980).…”
Section: Discussionmentioning
confidence: 53%
“…The homozygous eu3-e1/eu3-e1 mutant lacks the activities of all soybean ureases. Eu3/eu3-e1 heterozygous plants (Stebbins et al, 1991;Stebbins and Polacco, 1995) have urease levels similar to wild-type Eu3/Eu3 plants. All urease-negative eu3-e1/eu3-e1 seeds used in this study were derived from selfed Eu3/ eu3-e1 plants.…”
Section: Plant Materials and Germination/growth Conditionsmentioning
confidence: 97%
“…Consistently, it was reported that in soybean, half of the nitrogen from allantoate was released as urea, presumably during ureidoglycolate degradation (Todd and Polacco, 2004). However, earlier studies could not find any evidence for a urea intermediate in the course of ureide catabolism in soybean (Winkler et al, 1985(Winkler et al, , 1987Stebbins and Polacco, 1995).…”
mentioning
confidence: 49%
“…UGL or UGAH), with one predominating over the other. For example, in soybean, ureidoglycolate catabolism was approximately 95% via UGAH and approximately 5% via UGL; thus, urease did not appear to be essential for ureide catabolism in this species (Stebbins and Polacco, 1995), whereas in chickpea (Cicer arietinum) UGL appears to be the predominant path (Munoz et al, 2001). The accumulation of ureidoglycolate and quantitative reduction in urea from Ni-D foliage suggests that the UGL activity is being impaired.…”
Section: Ureidesmentioning
confidence: 99%